Staurochlamys (Neurolaeneae, Asteraceae): an endemic genus from Cerrado, Brazil - Bueno, Vinicius Resende; Dalastra, Claudenice Hilda; Buchoski, Monica Gomes (Phytotaxa, 2024)
Staurochlamys is a monospecific genus found exclusively in the Brazilian Cerrado, recognized by a unique morphological trait in the Asteraceae: the flattened involucre. Prior research into this genus has been limited, and this paper represents the first comprehensive investigation exclusively dedicated to it. This study presents a thorough morphological description of the species, a nomenclatural revision, insights into the species distribution, phenology, a preliminary evaluation of extinction risk, details related to risk assessment, and the species distribution modelling. Additionally, previously unlisted collections have been incorporated, with careful consideration of habitat details. The genus is reaffirmed as an exclusive component to the Brazilian Cerrado, bearing an ‘Endangered’ classification, and historical modeling has proposed a hypothesis to explain the outliers in its current distribution.